2012
DOI: 10.1016/j.placenta.2012.06.020
|View full text |Cite
|
Sign up to set email alerts
|

PAR-2 triggers placenta-derived protease-induced altered VE-cadherin reorganization at endothelial junctions in preeclampsia

Abstract: PAR-2 is a G-protein coupled protease receptor whose activation in endothelial cells (ECs) is associated with increased solute permeability. VE-cadherin is an endothelial specific junction protein, which exhibits a disorganized distribution at cell junction during inflammation and is a useful indicator of endothelial barrier dysfunction. In the present study, we tested the hypothesis that PAR-2 activation mediates placenta-derived chymotrypsin-like protease (CLP)-induced endothelial junction disturbance and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
4
1
Order By: Relevance
“…altered VE-cadherin expression, and permeability changes [52][53][54] show that PAR-2 activation causes the loss of junctional VE-cadherin resulting in barrier disruption, in contrast to the observed barrier protective activity of testisin observed in the present study. Future studies are required to investigate whether PAR-2 regulation could be involved in testisin-mediated barrier protection of the microvasculature, or whether other substrates are involved.…”
Section: Plos Onecontrasting
confidence: 95%
“…altered VE-cadherin expression, and permeability changes [52][53][54] show that PAR-2 activation causes the loss of junctional VE-cadherin resulting in barrier disruption, in contrast to the observed barrier protective activity of testisin observed in the present study. Future studies are required to investigate whether PAR-2 regulation could be involved in testisin-mediated barrier protection of the microvasculature, or whether other substrates are involved.…”
Section: Plos Onecontrasting
confidence: 95%
“…We also showed the association between the role of compromised PAR 1 , functional polymorphisms, and adverse pregnancy outcomes of preterm birth and repeated early pregnancy loss 42,43 . Others have shown, that PAR 2 sh RNA silencing attenuated vascular endothelial cadherin; VE‐cadherin reorganization in endothelial cell junctions, 44 the association of PAR 2 , and we have shown that birth and repeated early pregnancy loss 42 and inhibited the increased endothelial permeability and barrier dysfunction in PE.…”
Section: Discussionsupporting
confidence: 70%
“…It also enhances the binding of the iEVTs to the endothelial cells [46]. During arterial remodeling, VE-cad is upregulated in the evEVTs to enhance their trans-endothelial migration and invasion [30,74,75] while failure of the EVT to upregulate VE-cad is observed in the placentae of preeclamptic women [30,76,77]. The role of VE-cad in trophoblast differentiation is not known.…”
Section: Type I Classical Cadherinsmentioning
confidence: 99%